2014
DOI: 10.1063/1.4903879
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of a cold non-neutral plasma slab

Abstract: This is the published version of a paper published in Physics of Plasmas. Citation for the original published paper (version of record):Karimov, A., Yu, M., Stenflo, L. (2014) Expansion of a cold non-neutral plasma slab. Plasmas, 21(12) Expansion of the ion and electron fronts of a cold non-neutral plasma slab with a quasi-neutral core bounded by layers containing only ions is investigated analytically and exact solutions are obtained. It is found that on average, the plasma expansion time scales linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Here we adopt a nonperturbative approach by first making an ansatz (through trial and error and intuitive guessing) on the spatial structures of the electric and velocity fields, then solve the ordinary differential equations (ODEs) for the temporal evolution of the given structure. [10,11] It is found that large-amplitude surface oscillations can be excited on the expansion fronts. Our results should be applicable for identifying and interpreting pair-plasma expansion phenomena in space and laboratory plasmas, as well as in numerical simulations of the latter.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Here we adopt a nonperturbative approach by first making an ansatz (through trial and error and intuitive guessing) on the spatial structures of the electric and velocity fields, then solve the ordinary differential equations (ODEs) for the temporal evolution of the given structure. [10,11] It is found that large-amplitude surface oscillations can be excited on the expansion fronts. Our results should be applicable for identifying and interpreting pair-plasma expansion phenomena in space and laboratory plasmas, as well as in numerical simulations of the latter.…”
mentioning
confidence: 99%
“…As we are interested in the evolution of the fronts đť‘Ą p (𝑡) and đť‘Ą e (𝑡) of the cold electron and positron fluids as they expand into the vacuum, we shall adopt an integral approach similar to the momentum integral method of Karman for turbulent boundary layers in neutral fluids. [15] The hydrodynamic density and momentum conservation equations for the cold electron and positron plasmas are [10,11]…”
mentioning
confidence: 99%
See 1 more Smart Citation